Digital Preservation Strategies in Academic Libraries: Ensuring Long-Term Access to Scholarly Resources - Nurhidayah, Nurhidayah; Kurniasari, Endah; Purnomo, Adelaide Gracegefa (Knowledge Garden: International Journal of Library Studies, 2025)
Digital preservation is critical to academic library management, ensuring long-term access to scholarly resources and institutional knowledge. This study investigates the strategies, challenges, and technological advancements in digital preservation within academic libraries through a systematic review of 18 selected articles published between 2020 and 2025. The research aims to synthesize current practices, assess policy frameworks, and identify innovative technologies enhancing preservation workflows. The methodology involves qualitative content analysis and categorizing articles into thematic clusters, including preservation strategies, policy and regulation, data management, sustainability, and emerging technologies. The findings reveal that successful preservation strategies rely on robust metadata management, collaborative networks, and continuous skill development for library staff. The COVID-19 pandemic accelerated the need for flexible remote access and heightened data security measures while innovations like AI and blockchain streamline preservation processes. Policy frameworks, shaped by evolving international standards, provide a foundation for sustainable preservation practices across institutions. The study concludes that integrating policy, technology, and collaboration is essential for building globally connected preservation ecosystems. Future research should explore the scalability of emerging technologies and develop cost-effective strategies to support long-term academic preservation in resource-limited institutions.